2015
DOI: 10.52283/nswrca.ajbmr.20150503a01
|View full text |Cite
|
Sign up to set email alerts
|

IMPACT OF CELEBRITY ENDORSEMENTS ON CONSUMERS’ PURCHASE INTENTION: A Study of Indian Consumers

Abstract: The use of celebrity endorsements in advertising has become a trend and a perceived winning formula of corporate image building and product marketing. As existing media get increasingly cluttered, the need to stand out has become paramount and celebrities have proved to be the ideal way to ensure brand prominence. Research has shown that the use of celebrity endorsers brings many positive effects in terms of positive feelings towards the ad and the brand, a positive brand attitude and increased purchase intent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
3
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 35 publications
2
3
0
2
Order By: Relevance
“…Lafferty and Goldsmith (1999) state that the endorser credibility indirectly has a positive effect on brand attitudes through attitudes toward the advertising. Jin and Phua (2014) and Gupta et al (2015) found that the endorser credibility had a significant influence on purchase intentions.…”
Section: Data Analysis and Discussionmentioning
confidence: 99%
“…Lafferty and Goldsmith (1999) state that the endorser credibility indirectly has a positive effect on brand attitudes through attitudes toward the advertising. Jin and Phua (2014) and Gupta et al (2015) found that the endorser credibility had a significant influence on purchase intentions.…”
Section: Data Analysis and Discussionmentioning
confidence: 99%
“…Trustworthiness is a key to the effectiveness of the messenger, advertising messages will change the attitude of the audience if the audience believes in the messenger (Krisjanti, 2006). Gupta et al (2015) in their research stated that if a celebrity is honest when promoting a product, it will give consumers confidence in a product and can help marketers to increase consumer buying decision in a product or service.…”
Section: Trustworthiness and Consumer Buying Decision On Youtubementioning
confidence: 99%
“…Variable References Consumer Preference [11], [12] Attitude to green products [13]- [15] Subjective norm [14], [16] Perceived behavioral control [14], [17] Environmental knowledge [16], [18] Environmental care [16] Green Purchase Intention [9] The questionnaire consisted of 15 preliminary questions and 33 statements from each of the variables used in the study, namely consumer preferences, attitudes towards green products, subjective norms, perceived behavioral control, environmental knowledge, and environmental awareness. The questionnaire contains statements with selected answers in the form of a 4-Likert scale.…”
Section: Table 1 Research Variablesmentioning
confidence: 99%